FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA KONSENTRASI KEAHLIAN BEAUTY THERAPY SMKN 1 BUDURAN SEBAGAI TERAPIS KECANTIKAN BIDANG PERAWATAN TANGAN - Kanzha Kania Damayanti; Nieke Andina Wijaya; Sri Dwiyanti; Maspiyah (Program Studi Pendidikan Tata Rias, 2026)
The rapid development of beauty trends has increased the demand for professional workers in the beauty service industry, including hand care. SMKN 1 Buduran, through the Beauty Therapy Expertise Concentration, equips students with relevant skills. This study aims to analyze the influence of internal and external factors on the interest of 11th-grade Beauty Therapy students at SMKN 1 Buduran to become hand care beauty therapists. The research employed a quantitative inferential approach with a population of 35 students. Data were collected through an online Likert-scale questionnaire and analyzed using multiple linear regression to examine both partial and simultaneous effects.The results show that partially, the interest indicator (sig. 0.000) has a significant effect on student interest, while attention (sig. 0.978), experience (sig. 0.942), social environment (sig. 0.310), and educational environment (sig. 0.202) have no significant effect. Simultaneously, the significance value (sig. 0.000) indicates that internal and external factors together have a significant effect on student interest. The coefficient of determination (R²) of 0.677 demonstrates that 67.7% of the variation in student interest is explained by internal and external factors, while 32.3% is influenced by other factors beyond this study. This study concludes that student interest is strongly affected by internal factors, particularly the interest indicator, while simultaneously both internal and external factors play an important role in shaping students’ interest in pursuing a career as hand care beauty therapists.